Epidermophyton floccosum: nucleotide sequence analysis and antifungal susceptibility testing of 40 clinical isolates. Issue 11 (1st October 2019) - Ansari, Saham; Ahmadi, Bahram; Norouzi, Maryam; Ansari, Zohreh; Afsarian, Mohammad Hosein; Lotfali, Ensieh; Rezaei-Matehkolaei, Ali
Abstract : Purpose. Epidermophyton floccosum is an anthropophilic dermatophyte species, which is one of the common causative agents of dermatophytosis in different parts of the world. The aim of the present investigation was to evaluate the genetic diversity of E. floccosum strains isolated from different parts of Iran and to define the in vitro susceptibility profiles of seven antifungal drugs against these clinical isolates. Methodology. Forty clinical strains of E. floccosum isolated from 40 patients with dermatophytosis were subjected to DNA extraction and PCR amplification of the ITS rDNA region using universal primers ITS1 and ITS4. The in vitro activities of griseofulvin, itraconazole, voriconazole, posaconazole, caspofungin, ketoconazole and terbinafine were determined using a broth microdilution method according to the CLSI-M-38A2 protocol. Results. A mean genetic similarity of 99.5 % was found between E. floccosum strains, with intraspecies differences ranging from 0 to 3 nt. The geometric mean (GM) MICs and minimum effective concentrations (MECs) across all isolates were, in increasing order, as follows: terbinafine (GM=0.018 mg l −1 ), posaconazole (GM=0.022 mg l −1 ), itraconazole (GM=0.034 mg l −1 ) and voriconazole (GM=0.045 mg l −1 ), which had low MICs against all tested strains, whereas caspofungin (GM=0.22 mg l −1 ), ketoconazole (GM=0.41 mg l −1 ) and griseofulvin (GM=0.62 mg l −1 ) demonstrated higher MICs. Conclusion. Our study showed low intraspecies variation within strains of E. floccosum . Furthermore, terbinafine, posaconazole, itraconazole and voriconazole were shown to be the most potent antifungal drugs against E. floccosum strains.